AKTIVITAS ANTIFOTOOKSIDAN DAN KOMPOSISI FENOLIK DARI DAUN CENGKEH (Eugenia aromatic L.) - Lumingkewas, Meiske; Manarisip, Jeanette; Indriaty, Fetty; Walangitan, Amelia; Mandei, Judith; Suryanto, Edi (Sam Ratulangi University, 2014)
The objectives of the present research were evaluated effect of solvent extraction on antiphotooxidative from cloveleave (Eugenia aromatic (L). A certain quantity of powdered sample was extracted with methanol 80%, ethanol 80%and aseton 80%. After evaporation the extracts were dissolved in methanol and assayed for phenolic, flavonoid andcondensed tannin content. Singlet oxygen quenching and free radical activity of each extracts of spices at 500 ppmlevel were evaluated using 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical. Anti-photooxidative activity test wasconducted using linoleic acid as substrates each containing 5 ppm erythrosine as a photosensitizer. The resultshowed that solvent was significantly having effect on total phenolic, flavonoid and condensed tannin content.Methanol extract possessed highest total flavonoid and condensed tannin content than aseton and etanol. Methanolextract of clove leave was found to have the highest anti-photooxidative effect, followed by aseton and ethanol. Inaddition, ekstrak methanol showed any difference in it free radical scavenger effect than that of ethanol and asetonextracts. This results show that clove methanol extract has the best activity on photooxidation of linoleic acid andscavenger of free radical DPPH. These results suggest that the methanolic extract of clove leave contains somecompounds having singlet oxygen quenching and free radical scavenging activities on linoleic acid and free radicalDPPH.Penelitian ini bertujuan untuk mempelajari pengaruh pelarut ekstraksi terhadap aktivitas antifotooksidan dankomposisi fenolik yang terdapat pada ekstrak daun cengkeh. Serbuk daun cengkeh diekstraksi dengan metanol 80%,etanol 80% dan aseton 80%. Setelah evaporasi, ekstrak daun cengkeh dilakukan pengujian untuk kandungan fenolik,flavonoid dan tannin terkondensasi. Aktivitas penstabilan oksigen singlet dan radikal bebas dari ekstrak dievaluasidengan menggunakan asam linoleat sebagai substrat yang mengandung 5 ppm eritrosin sebagai fotosensitiser danradikal bebas 1,1-diphenyl-2-picrylhydrazyl (DPPH). Hasil penelitian ini menunjukkan bahwa pelarut ekstraksimemiliki efek sangat signifikan terhadap kandungan fenolik, flavonoid dan tannin terkondensasi. Pelarut ekstrakmetanol memiliki kandung flavonoid dan tannin terkondensasi paling tinggi daripada aseton dan etanol. Ekstrakmetanol daun cengkeh ditemukan mempunyai efek antifotooksidatif diikuti ekstrak etanol etanol dan aseton. Selainitu, pelarut methanol juga menunjukkan suatu perbedaan dalam penangkalan radikal bebas DPPH. Berdasarkananalisis komposisi fenolik dalam daun cengkeh dengan HPLC teridentifikasi senyawa eugenol, asam galat, kuersetin,rutin dan kaempferol. Hasil ini menyimpulkan bahwa ekstrak metanol daun cengkeh mengandung beberapasenyawa fenolik yang mempunyai aktivitas sebagai penstabilan oksigen singlet dan penangkalan radikal bebas.